Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae) - Wagner, Andre; Vuataz, Laurent; Sartori, Michel (Zootaxa, 2017)
A new species belonging to the speciose genus Electrogena Zurwerra & Tomka, 1985 is described based on all stages from material collected in Switzerland, northern Italy and Slovenia. Electrogena brulini Wagner sp. nov. is closely related to E. gridellii (Grandi, 1953). A genetic analysis based on the mitochondrial gene CO1, including 9 specimens from 5 populations, reveals a K2P distance of 22% between both species. Our investigations demonstrate that the description of the nymph of E. gridellii sensu Belfiore (1996) refers in fact to both species. Therefore, E. gridellii is redescribed in all stages. The number of bristles on each mandibular prostheca in the nymphs, the shape of titillators in male genitalia and the shape of the subanal plate in female imagines are the main characters allowing discrimination of these two species. This study also shows that in this case it is possible and helpful to use colour patterns to separate two closely related species. The re-examination of the type material of Electrogena vipavensis Zurwerra & Tomka, 1986 described from western Slovenia indicates that this species is a junior subjective synonym of E. gridellii.